Coaching Your Team in a Dynamic Workplace. - Gemma Leigh Roberts, Dr (linkedin.com, 2021)
Chartered psychologist Gemma Leigh Roberts teaches managers how to apply the most effect coaching skills in a constantly changing workplace.